Self-Defense in Climates of Fear - Weisbord, Noah (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2019)
Climates of fear—depleted inner cities, segregated rural communities, contested international hotspots—strain the law of self-defense, affecting legislation, policing, prosecution, and adjudication. There are distributional implications to our legislative and judicial choices, justifying or excusing some uses of deadly force but not others, making some segments of the population safer and others less so. Florida’s “Stand Your Ground” law, Canada’s “Lucky Moose” law, and the international law of self-defence provide three revealing examples. Our doctrinal preferences correspond with the cases and incidents that have most left their mark on us. As such, the law of self-defense is haunted by projections, pre-conceived notions about the world related to our past experiences rather than the situation at hand. This article, based on the author’s keynote lecture at the 2017 McGill Law Graduate conference, considers the challenge that fear poses to the law of self-defence.